An Implementation of Smartphone Based VTS - Yen-Jen Chen; Jun-Yi Lo (Journal of ICT, Design, Engineering and Technological Science, 2018)
This study proposes the development of an IoT application with computation, analysis, display, and notification mechanisms based on GPS, BLE, mobile communications, and SMS technology on iOS and Android smartphone operating systems. Advancements in smartphones and mobile communication technology have ushered in a generational trend of connectivity for all devices; using smartphones as a platform to manage vehicles online has become the trend. Smartphones using Bluetooth to bind vehicles and then send out GPS tracking information, including real-time data computation, analysis, display, and notifications, have turned IoT applications into reality. The research methods and procedure of this study are categorized into A) system structure, B) main application structure, C) QR code Bluetooth pairing, D) data processing, transfer, and retransmission mechanisms, and E) emergency incident and notification mechanisms. This study integrates QR code pairing, mo- bile notifications, Firebase Cloud Messaging (FCM), automatic retransmission mechanism for GPS tracking information, exception management, and emergency notification to achieve a lightweight electronic tracking and management App for implementing a Vehicle Tracking System on the smartphone. This study can be applied to all Bluetooth connected IoT applications; the principle is using smartphones and Bluetooth connectivity to connect items that cannot connect to networks.